2021
DOI: 10.1021/acs.jpcc.1c08108
|View full text |Cite
|
Sign up to set email alerts
|

In Situ X-Ray Diffraction Study on Hydrate Formation at Low Temperature in a High Vacuum

Abstract: The condition for incorporating simple gases with H2O to form clathrate hydrates in protosolar nebula is a subject of topical interest. Methane and carbon dioxide clathrate hydrates have been speculated to exist in outer solar system bodies, but they have eluded direct detection so far. We have constructed a low-temperature and high-vacuum system to prepare and study clathrate hydrates by in situ synchrotron X-ray diffraction experiments. Upon heating, we found clathrate hydrates can be obtained from the codep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The capability of forming these structures depends mainly upon the pressure and temperature conditions . Macroscopic deposits of hydrates generally occur at higher pressures, typically greater than 25 atm for methane. , CHs are also known to exist in vacuum, even under cryogenic conditions. In our previous study, we have shown the existence of sI methane hydrate at 30 K and 10 –10 mbar. Upon annealing the methane–water ice mixture deposited at 10 to 30 K for an extended period, methane CH was formed.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The capability of forming these structures depends mainly upon the pressure and temperature conditions . Macroscopic deposits of hydrates generally occur at higher pressures, typically greater than 25 atm for methane. , CHs are also known to exist in vacuum, even under cryogenic conditions. In our previous study, we have shown the existence of sI methane hydrate at 30 K and 10 –10 mbar. Upon annealing the methane–water ice mixture deposited at 10 to 30 K for an extended period, methane CH was formed.…”
Section: Introductionmentioning
confidence: 91%
“…While X-ray diffraction, differential scanning calorimetry, and Raman spectroscopy were typically used to examine CHs in bulk, , their existence in UHV is typically studied by infrared spectroscopy, temperature-programmed desorption mass spectrometry, and reflection high-energy electron diffraction performed on a thin film. Recently, Bauer et al showed the detection of methane and carbon dioxide CH in a high vacuum by in situ synchrotron X-ray diffraction . Cryo-electron microscopy has been used to examine the different crystalline states of water but has not been used yet for CH studies …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of clathrate hydrates (CHs) under high and ultrahigh vacuum (UHV) and cryogenic conditions is now well established. While CH of CO 2 at 120 K in a vacuum of 10 –6 to 10 –7 Torr has been known since 1991, the formation of CHs of CH 4 , , C 2 H 6 , CO 2 , , acetone, formaldehyde, and tetrahydrofuran (THF) in UHV has been observed in the past few years in the range of 10–130 K. CHs are crystalline host–guest inclusion compounds and have drawn wide interest due to their scientific and technological implications. CHs often coexist along with water ice and are mainly classified into structures I (sI, consisting of two small 5 12 and six large 5 12 6 2 cages per unit cell) and II (sII, consisting of 16 small 5 12 and eight large 5 12 6 4 cages per unit cell). While CO 2 is known to be encased in small 5 12 and large 5 12 6 2 cages, THF due to its larger van der Waals radius occupies the large 5 12 6 4 cage exclusively. ,,, In UHV, spectroscopic signatures of molecules in different hydrate cages (5 12 , 5 12 6 2 , and 5 12 6 4 ) were reported, , although these structures have not been confirmed by X-ray diffraction experiments.…”
mentioning
confidence: 99%
“…While CO 2 is known to be encased in small 5 12 and large 5 12 6 2 cages, THF due to its larger van der Waals radius occupies the large 5 12 6 4 cage exclusively. ,,, In UHV, spectroscopic signatures of molecules in different hydrate cages (5 12 , 5 12 6 2 , and 5 12 6 4 ) were reported, , although these structures have not been confirmed by X-ray diffraction experiments. However, in a high vacuum, in situ synchrotron X-ray diffraction experiments have been used to establish the existence of CHs of CH 4 and CO 2 . Various CHs could exist along with the water matrix, although their extended crystalline phase has not been observed, in UHV.…”
mentioning
confidence: 99%